Surface attachment, promoted by the actomyosin system of Toxoplasma gondii is important for efficient gliding motility and invasion - Whitelaw, Jamie A. (BMC Biol, 2017)
BACKGROUND: Apicomplexan parasites employ a unique form of movement, termed gliding motility, in order to invade the host cell. This movement depends on the parasite’s actomyosin system, which is thought to generate the force during gliding. However, recent evidence questions the exact molecular role of this system, since mutants for core components of the gliding machinery, such as parasite actin or subunits of the MyoA-motor complex (the glideosome), remain motile and invasive, albeit at significantly reduced efficiencies. While compensatory mechanisms and unusual polymerisation kinetics of parasite actin have been evoked to explain these findings, the actomyosin system could also play a role distinct from force production during parasite movement. RESULTS: In this study, we compared the phenotypes of different mutants for core components of the actomyosin system in Toxoplasma gondii to decipher their exact role during gliding motility and invasion. We found that, while some phenotypes (apicoplast segregation, host cell egress, dense granule motility) appeared early after induction of the act1 knockout and went to completion, a small percentage of the parasites remained capable of motility and invasion well past the point at which actin levels were undetectable. Those act1 conditional knockout (cKO) and mlc1 cKO that continue to move in 3D do so at speeds similar to wildtype parasites. However, these mutants are virtually unable to attach to a collagen-coated substrate under flow conditions, indicating an important role for the actomyosin system of T. gondii in the formation of attachment sites. CONCLUSION: We demonstrate that parasite actin is essential during the lytic cycle and cannot be compensated by other molecules. Our data suggest a conventional polymerisation mechanism in vivo that depends on a critical concentration of G-actin. Importantly, we demonstrate that the actomyosin system of the parasite functions in attachment to the surface substrate, and not necessarily as force generator. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12915-016-0343-5) contains supplementary material, which is available to authorized users.